Malta : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that Malta's economy continues to weather the global crisis well. Real GDP growth has been one of the highest in the euro area since the beginning of the crisis, supported by relatively diversified exports, a recent recovery in domestic demand, and a stable banking sector. Unemployment is close to historical lows and among the lowest in the euro area. The external position is strong, and progress has been achieved in reducing the budget deficit. The macroeconomic outlook is favorable. Growth is expected to remain robust in 2015-16, supported by domestic demand. Inflation is projected to remain subdued. The current account surplus will likely persist.